2002
DOI: 10.1097/00004770-200205000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up of Cases Considered Healed One Year After Apical Microsurgery

Abstract: A previous report demonstrated 96.8% healing within 1 yr after apical surgery was performed with the surgical operating microscope and Super-EBA as the root-end filling material. The purpose of this paper is to report on the long-term follow-up of those cases that were considered healed at the short term. Clinical examinations were made and radiographs were evaluated 5 to 7 yr after the case had first been considered healed. Criteria for determining healed cases were the same as those used in the first report.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
157
0
9

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(176 citation statements)
references
References 15 publications
10
157
0
9
Order By: Relevance
“…However, the degree of inflammation was extremely mild and the bone resorption was not significantly different among the SB, EBA, and MTA groups. As Rubinstein et al 31) reported long-term success when using reinforced zinc oxide eugenol cement as the root-end filling material, a few inflammatory cells facing reinforced zinc oxide eugenol cement might be clinically acceptable 32) . In contrast, reinforced zinc oxide eugenol cement has been reported to have inadequate long-term sealing ability 6,10) .…”
Section: Discussionmentioning
confidence: 99%
“…However, the degree of inflammation was extremely mild and the bone resorption was not significantly different among the SB, EBA, and MTA groups. As Rubinstein et al 31) reported long-term success when using reinforced zinc oxide eugenol cement as the root-end filling material, a few inflammatory cells facing reinforced zinc oxide eugenol cement might be clinically acceptable 32) . In contrast, reinforced zinc oxide eugenol cement has been reported to have inadequate long-term sealing ability 6,10) .…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Recently, at our institution, Kim et al reported a 91.5% overall success rate in 188 apicoectomy with retrofilling cases. 5 They considered the cases successful when there was the absence of clinical signs and/or symptoms and radiographic evidence of complete or incomplete healing.…”
Section: Introductionmentioning
confidence: 87%
“…Another study points to an even greater discrepancy of 44.2%-60% for the traditional method and 91.1% for microsurgical techniques. [37,38].…”
Section: Microsurgical Apicoectomymentioning
confidence: 99%